2016
DOI: 10.4103/1319-3767.182459
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of the methanolic extract of malva parviflora l. leaves on acetic acid-induced ulcerative colitis in rats

Abstract: Background/Aims:Inflammatory bowel disease (IBD) is a general term describing chronic, idiopathic relapsing, inflammatory conditions of the gastrointestinal tract of unknown etiology. Previous studies have indicated that Malva parviflora leaf extract possesses anti-inflammatory, antioxidant, and antiulcerogenic activity. activity. This work aimed to investigatee the anti-inflammatory effect of the methanolic (MEMP) and aqueous (AEMP) extracts of M. parviflora leaves on acetic acid-induced colitis in rats.Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Chronic UC was induced as described [15]: animals were induced by 2 rectal applications of 4% acetic acid (1 mL) weekly. After administration, the rats were held upside down for approximately 30 seconds to prevent immediate leakage of the agent from the anus.…”
Section: Methodsmentioning
confidence: 99%
“…Chronic UC was induced as described [15]: animals were induced by 2 rectal applications of 4% acetic acid (1 mL) weekly. After administration, the rats were held upside down for approximately 30 seconds to prevent immediate leakage of the agent from the anus.…”
Section: Methodsmentioning
confidence: 99%
“…Antioxidants are suggested to beneficially interfere with diseases or drugs-related oxidative stress [44]. M. verticillata contains a higher total content of flavonoids compared with phenolic components according to the previous studies [9,45]. naturally existing in some plants, and abundantly in M. verticillata [46].…”
Section: Discussionmentioning
confidence: 99%
“…8,9) In Mexico this plant is distributed all over the country and the ethnobotanical uses are diverse, it is used for treating wounds, bruises, abscesses, fever, headaches, cold sores, infections and for renal problems. 10) This plant has not been widely studied, some pharma-cological effects are attributed to it such as, anti-inflammatory activity on cyclooxygenase-1 and -2 (COX-1 and COX-2) and other studies demonstrated that the extracts inhibited ear oedema induced with croton oil, 8) as well as, inhibiting the vascular permeability induced with acetic acid, also presenting in a dose dependent form a strong scavenging activity against free radical 2,2-diphenyl-1-picrilhidrazil (DPPH). 9) Methanol extract of M. parviflora also reduces mucosal damage in an experimental colitis assay.…”
Section: Introductionmentioning
confidence: 99%
“…12) Even though M. parviflora is widely used in traditional medicine and pharmacological studies have been made, the chemical composition has not been completely identified; only some fatty acids: malvalic, sterculic and vernolic acids, as well as, some anthocyanins and phenolic compounds have been reported. 10,13) In this work were evaluated the anti-hypertensive activity of extracts and fractions from M. parviflora by using a chronic model of hypertension induced by angiotensin II (AGII), and in this same assay was measured the capacity of the plant for to modified the concentration of cytokines in kidneys, as well as the lipid peroxidation. And the other hand, was made a chemical separation of the most active fraction and two compounds were isolated by chromatographic column, these substances were tested in an acute hypertension-induced with AGII in mice.…”
Section: Introductionmentioning
confidence: 99%